PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP PROFITABILITAS PERUSAHAAN STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM BURSA EFEK INDONESIA - Mochammad Fauzan Adhima, SE; Bambang Hariadi, SE., M.Ec., Ak. (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aims to obtain empirical evidence about the effect of disclosure Sustainability Report (SR),  the disclosure of  environmental performance,  social performance  and disclosure  on the profitability of  the company.  Disclosure Sustainability  Report (SR),  the disclosure of  environmental performance  and social performance disclosure was measured using the Global Reporting Initiative Guidelines  G-3  (G-3  GRI  Guidelines).  Profitability  measured using  Return on Assets (ROA). The population in this study is manufacturing companies listed in the  Indonesia Stock Exchange  (IDX) during the period 2009-2011. Total sample is 26  firms determined by the method of purposive  sampling. Data analysis was performed  by testing  the classical  assumptions  and hypothesis testing  using multiple linear regression analysis.  The results of  this study indicate  that the disclosure  of  Sustainability  Report (SR)  and the  disclosure of  environmental performance  have  significant  positive  impact  on Return  on Assets  (ROA). Meanwhile, the disclosure of social performance has significant negative effect on Return on Assets (ROA). Keywords: Disclosure  Sustainability Report (SR), Disclosure of  environmental performance,  social performance  disclosure,  Profitability, Return  on Assets (ROA).